Digital supplementation in language education: Evaluating mobile application’s impact in large classroom settings - Tjahyanto, Mario Christian Noer; Hartanto, Yenny (Journal of Applied Studies in Language, 2024)
Integrating digital tools into language education has transformed traditional teaching methods, offering greater flexibility, increased engagement, and personalized learning opportunities. This study explored how effective Duolingo can be as a supplementary tool in a large speaking class of 60 first-year undergraduate Informatics Engineering students at a university. With the challenges of managing a large group and varying levels of language proficiency, the study used a descriptive qualitative approach over half of the semester to assess Duolingo's impact on student engagement, motivation, and English proficiency. Data were gathered through Duolingo’s tracking system, weekly self-reflection reports, in-class observations, and informal interviews. The analysis revealed that Duolingo significantly boosts student motivation and provides valuable practice opportunities outside the classroom, especially in vocabulary and grammar. The quantitative data showed consistent student engagement, with many students regularly earning experience points (XP) and meeting their weekly learning targets. However, the study also highlighted some challenges, such as Duolingo’s limited focus on developing conversational skills and the difficulty of addressing the varied proficiency levels within such a large class. While students enjoyed the gamified aspects of Duolingo, they expressed a need for more interactive speaking exercises to help build fluency. Overall, the findings suggest that Duolingo is a useful supplement to traditional language instruction, enhancing engagement and offering personalized practice.